Meiotic crossovers characterized by haplotype-specific chromosome painting in maize - do Vale Martins, Lívia (Nat Commun, 2019)
Meiotic crossovers (COs) play a critical role in generating genetic variation and maintaining faithful segregation of homologous chromosomes during meiosis. We develop a haplotype-specific fluorescence in situ hybridization (FISH) technique that allows visualization of COs directly on metaphase chromosomes. Oligonucleotides (oligos) specific to chromosome 10 of maize inbreds B73 and Mo17, respectively, are synthesized and labeled as FISH probes. The parental and recombinant chromosome 10 in B73 x Mo17 F(1) hybrids and F(2) progenies can be unambiguously identified by haplotype-specific FISH. Analysis of 58 F(2) plants reveals lack of COs in the entire proximal half of chromosome 10. However, we detect COs located in regions very close to the centromere in recombinant inbred lines from an intermated B73 x Mo17 population, suggesting effective accumulation of COs in recombination-suppressed chromosomal regions through intermating and the potential to generate favorable allelic combinations of genes residing in these regions.